Ultrasonic Extraction of Oil from Caesalpinia spinosa (Tara) Seeds - Zhan-jun Li; Feng-jian Yang; Lei Yang; Yuan-Gang Zu (Journal of Chemistry)
Oil extracted from the seeds of Caesalpinia spinosa (common name: tara) can be used in a number of applications. In the present study, tara seed oil was obtained by ultrasonic extraction. The effects of different solvents, particle sizes in the ground seed samples, extraction times, ultrasonication powers, extraction temperatures, and liquid–solid ratios on the yield of tara seed oil were investigated. The yield from the ultrasonic extraction was compared with that from traditional Soxhlet extraction. The results showed that ultrasonic extraction could be completed in a shorter time with reduced solvent consumption. The yield of tara seed oil increased with increasing ultrasonication power and extraction temperature. Gas chromatography was used to analyze the fatty acid compositions of the oils extracted by the two methods. The fatty acid compositions of the oils from both extraction methods were similar, which indicates that ultrasonic extraction is a viable alternative means of extraction. It is a rapid, efficient, and simple method for production of lipids from tara seeds.